Replication of an association between the lymphoid tyrosine phosphatase locus (LYP/PTPN22) with type 1 diabetes, and evidence for its role as a general autoimmunity locus. - Smyth, D; Cooper, J; Collins, J; Heward, J; Franklyn, J; Howson, J; Vella, A; Nutland, S; Rance, H; Maier, L; Barratt, B; Guja, C; et al. (2004)
In the genetic analysis of common, multifactorial diseases, such as type 1 diabetes, true positive irrefutable linkage and association results have been rare to date. Recently, it has been reported that a single nucleotide polymorphism (SNP), 1858C>T, in the gene PTPN22, encoding Arg620Trp in the lymphoid protein tyrosine phosphatase (LYP), which has been shown to be a negative regulator of T-cell activation, is associated with an increased risk of type 1 diabetes. Here, we have replicated these findings in 1,388 type 1 diabetic families and in a collection of 1,599 case and 1,718 control subjects, confirming the association of the PTPN22 locus with type 1 diabetes (family-based relative risk (RR) 1.67 [95% CI 1.46-1.91], and case-control odds ratio (OR) 1.78 [95% CI 1.54-2.06]; overall P = 6.02 x 10(-27)). We also report evidence for an association of Trp(620) with another autoimmune disorder, Graves' disease, in 1,734 case and control subjects (P = 6.24 x 10(-4); OR 1.43 [95% CI 1.17-1.76]). Taken together, these results indicate a more general association of the PTPN22 locus with autoimmune disease.